The role of robotic gait training and tDCS in Friedrich ataxia rehabilitation: A case report. Issue 8 (February 2019) - Portaro, Simona; Russo, Margherita; Bramanti, Alessia; Leo, Antonio; Billeri, Luana; Manuli, Alfredo; La Rosa, Gianluca; Naro, Antonino; Calabrò, Rocco Salvatore
Abstract: Rationale: Friedrich ataxia (FA) is the most common inherited neurodegenerative cerebellar ataxic syndrome. In patients with FA, physiotherapy is highly recommended to improve motor function outcome. Cerebellar transcranial direct current stimulation (tDCS) has been demonstrated to be effective in improving symptoms by modulating cerebellar excitability. Recently, robotic rehabilitation with Lokomat-Pro has been used to treat motor impairment in ataxic syndromes by "modulating" cortical plasticity and cerebello-motor connectivity. Patient concerns: A 29-year-old Italian male with FA, come to our Institute to undergo intensive rehabilitation training. He presented a moderate-to-severe spastic tetraparesis, brisk deep tendon reflexes, moderate dysarthria, occasional difficulty in speaking, and mild delay in swallowing. He was able to stand for at least 10 seconds in the natural position with constant support, and thus he used a wheelchair. Diagnosis: Tetraparesis in a young patient with FA. Interventions: The effects of a stand-alone robotic gait training with Lokomat-Pro preceded by cerebellar anodal tDCS (a-tDCS) versus Lokomat-Pro preceded by cathodal-tDCS (c-tDCS) are compared. Outcomes: The coupled approach (i.e., tDCS and Lokomat) demonstrated better improvement in functional motor outcomes on the Scale for the Assessment and Rating of Ataxia (SARA). Lessons: Although only a single case is described, we found that the combined neuromodulation-neurorobotic approach could become a promising tool in the rehabilitation of cerebellar ataxias, possibly by shaping cerebello-cerebral plasticity and connectivity.